Parallel Speciation of Wild Rice Associated with Habitat Shifts. (12th March 2019) - Cai, Zhe; Zhou, Lian; Ren, Ning-Ning; Xu, Xun; Liu, Rong; Huang, Lei; Zheng, Xiao-Ming; Meng, Qing-Lin; Du, Yu-Su; Wang, Mei-Xia; Geng, Mu-Fan; Chen, Wen-Li; et al.
Abstract: The occurrence of parallel speciation strongly implies the action of natural selection. However, it is unclear how general a phenomena parallel speciation is since it was only shown in a small number of animal species. In particular, the adaptive process and mechanisms underlying the process of parallel speciation remain elusive. Here, we used an integrative approach incorporating population genomics, common garden, and crossing experiments to investigate parallel speciation of the wild rice species Oryza nivara from O. rufipogon . We demonstrated that O. nivara originated multiple times from different O. rufipogon populations and revealed that different O. nivara populations have evolved similar phenotypes under divergent selection, a reflection of recurrent local adaptation of ancient O. rufipogon populations to dry habitats. Almost completed premating isolation was detected between O. nivara and O. rufipogon in the absence of any postmating barriers between and within these species. These results suggest that flowering time is a "magic" trait that contributes to both local adaptation and reproductive isolation in the origin of wild rice species. Our study thus demonstrates a convincing case of parallel ecological speciation as a consequence of adaptation to new environments.